Confocal Assessment of Pigmented-Mucosal Lesions: A Monocentric, Retrospective Evaluation of Lip and Genital Area - Coco, Valeria; Cappilli, Simone; Di Stefani, Alessandro; Ricci, Costantino; Perino, Francesca; Di Nardo, Lucia; Longo, Caterina; Peris, Ketty (Dermatology practical & conceptual, 2024)
Introduction: Pigmentation of lip and/or genitalia is mainly due to the development of benign melanotic macules, with a less occurrence of melanocytic and other non-melanocytic lesions. Mucosal melanoma has worse prognosis compared with cutaneous counterpart, hence identification of atypical features for an early diagnosis is crucial. Objectives: The aim of this study was to report further data of confocal features characterizing pigmented mucosal lesions of genital area and of the lips and test the diagnostic role of the reflectance confocal microscopy (RCM)lip score. Methods: Clinical, dermoscopic and RCM images of histologically proven pigmented lesions, involving the genital area (vulva or glans penis) and lip, were retrospectively reviewed. RCM images were evaluated for malignant criteria, and statistical analysis was conducted for categorical variables. Results: Seventy pigmented lesions were included in the study and divided into two groups based on the body area location: lip (17) and genital area (53). Architectural disarray (P = 0.002), dendritic (P = 0.031) and roundish cells in epidermis (P < 0.0001), interpapillary dendritic cells (P = 0.039) and junctional atypical cells (P = 0.002) were associated to genital melanoma. Melanoma involving the lip was characterized by roundish cells in epidermis, a criterion found in one labial benign lesion, only (P = 0.005). Main limitations of the study are the inclusion of low melanomas and the presence of epidermal dendritic cells in melanosis and melanoma, as a confusing factor in imaging. Conclusions: Dermatologists should consider confocal microscopy as an adjunctive tool to dermoscopy in the differential diagnosis of pigmented mucosal lesions, especially in presence of clinical and dermoscopic findings suspicious for malignancy.